2017
DOI: 10.1038/srep43781
|View full text |Cite
|
Sign up to set email alerts
|

Plumbagin sensitizes breast cancer cells to tamoxifen-induced cell death through GRP78 inhibition and Bik upregulation

Abstract: The glucose regulated protein 78 (GRP78) is a major chaperone of the endoplasmic reticulum, and a prosurvival component of the unfolded protein response. GRP78 is upregulated in many types of cancers, including breast cancer. Research has suggested that GRP78 overexpression confers chemoresistance to anti-estrogen agents through a mechanism involving the inhibition of a pro-apoptotic BH3-only protein, Bik. In the present research the role of plumbagin, a naturally occurring naphthoquinone, in GRP78-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…Our data seems to be consistent with research conducted in breast cancer. The researchers proposed that plumbagin (anticancer drug) induces apoptosis in estrogenpositive breast cancer cells through HSPA5 (GRP78) inhibition (18). Nevertheless, in accordance to our studies afatinib by itself induces apoptosis and mRNA level of HSPA5 decreases.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our data seems to be consistent with research conducted in breast cancer. The researchers proposed that plumbagin (anticancer drug) induces apoptosis in estrogenpositive breast cancer cells through HSPA5 (GRP78) inhibition (18). Nevertheless, in accordance to our studies afatinib by itself induces apoptosis and mRNA level of HSPA5 decreases.…”
Section: Discussionsupporting
confidence: 88%
“…In our results, it seems that apoptosis is caused by afatinib treatment and HSPA5 mRNA level reduction depends on morphological changes. However, our interpretations require further experiments, although it appears there is some connection between anticancer drugs apoptotic effect and HSPA5 in cancer cells (18).…”
Section: Discussionmentioning
confidence: 77%
“…For this reason, the development of specific BiP inhibitors represents an important goal. In fact, a natural product of the naphthoquinone family, plumbagin, was identified that initiates cell death in ER-positive breast cancer cells by upregulating BIK levels [ 219 , 220 ]. Plumbagin-mediated BiP inhibition also sensitized breast cancer cells to tamoxifen-mediated cell death.…”
Section: Bip Upregulation Is a Marker For Drug Resistance In Breast Cmentioning
confidence: 99%
“…Plumbagin-mediated BiP inhibition also sensitized breast cancer cells to tamoxifen-mediated cell death. In addition, BiP knock down impaired the plumbagin-mediated increase in Bik, suggesting an inhibitory role of this compound on BiP-mediated downregulation of BIK in breast cancers [ 220 ]. Overall, BiP is emerging as a novel target to predict cancer outcomes and therapeutic options [ 209 , 221 223 ].…”
Section: Bip Upregulation Is a Marker For Drug Resistance In Breast Cmentioning
confidence: 99%
“…Another emerging target is the cytosolic Hsp70 molecular chaperone, which is upregulated in many cancers and inhibits multiple steps in the apoptotic pathway (Garrido et al, 2006;Santarosa et al, 1997;Uozaki et al, 2000). Inhibition of Hsp70 or the ER luminal homolog, BiP (also known as GRP78 and HSPA5), kills colorectal carcinomas, breast cancers, leukemia cells, glioblastomas and ovarian cancer cells (Cerezo et al, 2016;Guo et al, 2005;Kawiak et al, 2017;Lee, 2001Lee, , 2007Ni et al, 2009;Powers et al, 2008Powers et al, , 2009Sabnis et al, 2016). Furthermore, Hsp70 promotes chemotherapeutic resistance, and Hsp70 induction predicts metastasis in several cancers (Brodsky and Chiosis, 2006;Calderwood and Gong, 2016;Nanbu et al, 1998;Patury et al, 2009;Powers et al, 2009).…”
Section: Introductionmentioning
confidence: 99%